STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKULKARIMAH SISWA - Badrudin Kamil; Ahmad Busyairi (Karimiyah: Journal of Islamic Literature and Muslim Society, 2024)
Education is a very urgent activity in Islam. With education, Islam can be spread and accepted by humans. Education has been mentioned in the Qur'an and hadith. In the Al-qu'an, Surah An-Nahl verse 125, apart from ordering Muslims to preach, it also provides guidance on how to carry it out, namely in a good way and in accordance with religious instructions. In this discussion, the methods used are the methods of deduction and induction, and are described qualitatively. The discussion on writing this thesis is through research consisting of library research and literature discussion (theory). Served as a basis and feedback from the actual situation in the discussion. This literature research was carried out in research intended to obtain direct descriptions and situations as material for obtaining the input presented. Based on the statements put forward by the author in the research, the author came to the conclusion that education can be interpreted as a process of conveying it to students so that students want or know about the Islamic religion. The law of seeking knowledge is fardhu a'in. In teaching, there are the most important assets, namely having knowledge, being gentle and patient.